2015
DOI: 10.1039/c5ob01560j
|View full text |Cite
|
Sign up to set email alerts
|

An efficient aldol-type direct reaction of isatins with TMSCH2CN

Abstract: Cesium fluoride catalyzed direct cyanomethylation of various isatins by using trimethylsilyl acetonitrile (TMSAN) as a nucleophile has been developed. The reaction has been explored for a number of isatins, with various substitutions on its aromatic ring. Further, the versatility of the reaction is demonstrated by converting the direct aldol adducts to the corresponding intermediates of natural products and medicinally important compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 93 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…S1). Further, 25 compounds from isatin in-house library [39] were docked and scored against HAV 3C protease to check for their inhibitory potential. All isatin compounds showed low binding potential computationally; hence iterative modifications in their structure were undertaken.…”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…S1). Further, 25 compounds from isatin in-house library [39] were docked and scored against HAV 3C protease to check for their inhibitory potential. All isatin compounds showed low binding potential computationally; hence iterative modifications in their structure were undertaken.…”
Section: Computational Methodologymentioning
confidence: 99%
“…An indole backbone, with various substituents on the core structure, has the ability to display a spectrum of functionalities. In particular, and due to their broad structural diversity, isatins have been shown to affect a wide range of biological targets [35][36][37][38][39]. We computationally screened a variety of isatin derivatives against HAV 3C protease, and found that two modifications in the protecting groups of isatins (in compounds 8 and 9; Table 1) resulted in better interactions with the target, as reflected in docking studies as well as in the 100 ns molecular dynamics simulations.…”
Section: Novel Isatin-based Compounds Against Hav 3cmentioning
confidence: 99%
“…Recently, aryl- and trifluoromethyl-substituted tertiary alcohols were synthesized by the aldol reaction of ketones as donor and aryl trifluoromethyl ketone as acceptor in the presence of DBU as catalyst . Recently, our group as well as others have demonstrated the cyanomethylation by using TMSAN (trimethylsilyl acetonitrile) as the cyanomethylating agent . Here, we report DBU-mediated direct alkylnitrile addition to isatins, a facile access to 3-hydroxy-3-cyanomethyl oxindoles.…”
mentioning
confidence: 99%